Pollen development under control and high-temperature stress: the role of plant hormones - Dhirendra Fartyal; Ashleigh Crane; Hagai Yasuor (Plant Stress, 2025)
Pollen grains, the sperm cell dispersal vectors, are essential for sexual reproduction and subsequent fruit and seed production. The developmental processes that release functional pollen at the precise stage and time to maximize pollination and fertilization are crucial for plant reproduction and genetic diversity. Male gametophyte development is a complex process highly susceptible to environmental chaos. Normal male gametogenesis and pollen development processes are affected by the sporophyte function, and both tissues demonstrate susceptibility to abiotic stress, mainly high-temperature (HT) stress. In addition to male flower organs, pollen interactions with female flower organs (stigma and style) are also crucial for ensuring pollination, fertilization, and proper seed development, where hormones play a pivotal role, generally via complex hormonal cross-regulation and crosstalk under both normal and HT conditions. This review encapsulates our current knowledge of the roles of phytohormones in male gametophyte development and function under normal conditions, HT-induced injuries/modifications, and specific hormonal responses during pollen development, pollen germination, and fertilization under HT stress. It finally culminates in raising some crucial questions that further need to be understood to mitigate the effects of HT stress and increase crop yield by utilizing the knowledge of functional aspects of phytohormones.